2005
DOI: 10.1002/gps.1428
|View full text |Cite
|
Sign up to set email alerts
|

Late‐life depression: the differences between early‐ and late‐onset illness in a community‐based sample

Abstract: In a community-based sample we did not detect clear differences in etiology and phenomenology between EOD and LOD. This discrepancy with reports from clinical samples could be due to selection bias in clinical studies. Consequently, all patients with late-life depression deserve a diagnostic work-up of both psychosocial and somatic risk factors and treatment interventions should be focused accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 47 publications
1
37
0
Order By: Relevance
“…The finding of increased cognitive impairment in subjects with late onset depression has also been reported by other investigators (Salloway et al, 1996, Lesser et al, 1996 although a large number of studies have not demonstrated this finding (Brodaty et al, 2001, Baldwin andTomenson, 1995). Specifically, with regard to studies based in the community dwelling elderly, one study using similar methodology found an association between later age of onset and cognitive impairment (van Ojen et al, 1995a) while another found no significant association after adjustment for confounders (Janssen et al, 2006). It has been argued that differences in selection processes and methodology may account for some of this variability in research findings (Brodaty et al, 2001).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The finding of increased cognitive impairment in subjects with late onset depression has also been reported by other investigators (Salloway et al, 1996, Lesser et al, 1996 although a large number of studies have not demonstrated this finding (Brodaty et al, 2001, Baldwin andTomenson, 1995). Specifically, with regard to studies based in the community dwelling elderly, one study using similar methodology found an association between later age of onset and cognitive impairment (van Ojen et al, 1995a) while another found no significant association after adjustment for confounders (Janssen et al, 2006). It has been argued that differences in selection processes and methodology may account for some of this variability in research findings (Brodaty et al, 2001).…”
Section: Discussionmentioning
confidence: 96%
“…The majority of studies which have examined age of onset of depressive disorder in relation to phenomenological and aetiological variables have either included patients who self-presented to primary care or were referred for specialist treatment. To the best of our knowledge, only a small number of studies have examined these hypotheses in community-based samples (Janssen et al, 2006, van Ojen et al, 1995b, Corruble et al, 2008. Given that a minority of patients with depression in the community are referred to secondary care and that such patients tend to have more severe and enduring illness means that findings from hospital samples may not necessarily generalise to community populations (Eustace et al, 2001).…”
Section: Introductionmentioning
confidence: 97%
“…Not all studies find an association between late-onset depression and vascular pathology. Janssen et al (2006) found no such association in an elderly (55-85 years of age) community-based sample. However, this may be explained by the possibility that depression in a community sample is less likely to be complicated by factors such as comorbid vascular disease.…”
Section: Vascular Diseasementioning
confidence: 68%
“…People with early-onset depression tend to have more depressive cognitions, including suicidal thoughts, thoughts of worthlessness (Reinhard et al, 2000;Janssen et al, 2006) and neuroticism (Baldwin & Tomenson, 1995;Van den Berg et al, 2001). Individuals with late-onset depression tend to present more with symptoms of psychomotor change, anhedonia, cognitive impairments (Hickie et al, 2001;Rapp et al, 2005) and weight loss (Janssen et al, 2006).…”
Section: Depressed Mood and Cognitionsmentioning
confidence: 99%
See 1 more Smart Citation